1992
DOI: 10.3758/bf03212235
|View full text |Cite
|
Sign up to set email alerts
|

Interpolation in structure from motion

Abstract: We investigated surface interpolation in displays of structure from motion (SFM). To do so, we introduced a new method for measuring surface perception in dynamic displays-the SFM probe. An SFM probe is a dot that moves rigidly with the dots on a simulated surface, and whose distance from that surface can be adjusted with a joystick or similar control. The displays we studied were random-dot cylinders containing a vertical strip devoid offeature points (the gap). Subjects adjusted an SFM probe, presented in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
7
0

Year Published

1993
1993
1997
1997

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(8 citation statements)
references
References 38 publications
1
7
0
Order By: Relevance
“…The present results suggest that the internal noise in the visual system is reduced by integrating over space. This is in agreement with experiments on surface interpolation (Husain, Treue, & Anderson, 1989;Saidpour, Braunstein, & Hoffman, 1992), which indicate that the visual system can integrate motion information spatially for SfM. Thresholds expressed in the maximum angular difference between the displacement vectors with the mean direction (after removal of global rotation and magnification) are largely independent of the wavelength.…”
Section: Discussionsupporting
confidence: 76%
“…The present results suggest that the internal noise in the visual system is reduced by integrating over space. This is in agreement with experiments on surface interpolation (Husain, Treue, & Anderson, 1989;Saidpour, Braunstein, & Hoffman, 1992), which indicate that the visual system can integrate motion information spatially for SfM. Thresholds expressed in the maximum angular difference between the displacement vectors with the mean direction (after removal of global rotation and magnification) are largely independent of the wavelength.…”
Section: Discussionsupporting
confidence: 76%
“…Our previous study of surface interpolation (Saidpour et al, 1992) used stimuli similar to those of the present study, with one difference: the dots in the previous study lay on the surface of a cylinder rather than on a dihedral angle. In that study, we found that subjects placed the probe dot significantly outside a true cylindrical interpolation.…”
Section: Discussionmentioning
confidence: 99%
“…In a previous study of surface interpolation in SFM, Saidpour, Braunstein, and Hoffman (1992) used stimuli similar to Grimson's half cylinders. The displays were orthographic projections of dots on the surface of half cylinders rotating back and forth ±19°about a vertical axis through the center of the cylinder.…”
mentioning
confidence: 99%
“…The companion paper (Hildreth, Ando, Andersen & Treue, 1995) provides a discussion of possible implementations of such a process (see also Ando, 1992;Hildreth, Ando, Andersen & Treue, 1991). Recently, Saidpour, Braunstein and Hoffman (1992) also described interpolation in the perception of SFM.…”
Section: Introductionmentioning
confidence: 99%